The Effect of Zimbabwe's Multi-Currency Arrangement on Bilateral Trade: Myth versus Reality. - Buigut, Steven (International Journal of Economics and Financial Issues, 2015)
To tame the hyperinflation experienced in the country, Zimbabwe adopted a relatively unique solution by implementing a multi-currency system in January 2009. Five foreign currencies were granted official status. However, this arrangement is viewed as a temporary measure to restore stability and there is no commitment by authorities to maintain it long term. The present study uses a theoretically consistent gravity model that accounts for endogeneity, to estimate the effect of the multi-currency arrangement implemented in Zimbabwe on bilateral trade. The period covered by the study is from 2004 to 2012 using a total of 50 potential trading partners from Africa, Asia, Western Europe, Eastern Europe, North and South America. The results suggest that the multi-currency arrangement as adopted has depressed Zimbabwe's bilateral trade by nearly 15 percent. Keywords: multi-currency regime; gravity model; trade, Zimbabwe. JEL Classifications: F14; F15; F33